ANALISIS PENGARUH CASH RATIO, DEBT TO EQUITY RATIO, RETURN ON ASSET, FIRM SIZE DAN GROWTH OPPORTUNITY TERHADAP KEBIJAKAN DIVIDEN (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2009 – 2013) - Septiana, Miladia; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2015)
This study analyzed the impact of cash ratio, debt to equity ratio, return on assets, firm size, and growth opportunity to the dividend policy on manufacturing companies listed on Stock Exchange of Indonesiafrom 2009 to 2013. The cash ratio as a measurement of liquidity, debt to equity ratio as a measurement of leverage, return on assets as a measurement of profitability, firm size was measured by log natural of total assets and growth opportunity was measured by market to book ratio.The sampling technique is using purposive sampling method by using 18 manufacturing companies which pay dividend continuosly. The analysis technique is using multiple regression.The result of this study shows that cash ratio and debt-to-equity ratio were found to be positive and no significant effect.Return on assets and growth opportunity were found to be positive and have significant effect to the dividend payout ratio, while firm size were fount to be negative and have significant effect to the dividend payout ratio.